Social dimension of inclusive growth in ECOWAS: Implication for poverty reduction - Toriola K. Anu; Goerge O. Emmanuel; Ajayi O. Felix (CBN Journal of Applied Statistics, 2022)
This study investigates the implication of the social dimension of inclusive growth on poverty reduction in Economic Community of West African States (ECOWAS) coun- tries. It specifically examines how social indices of inclusive growth comprising of in- come inequality, education, and health outcomes affect poverty reduction. The study uses a panel dataset of the six (6) lower-middle income countries in ECOWAS which was analysed via panel Difference Generalised Method of Moment (D-GMM). The results show that GDP per capita exerts significant negative effect on poverty while inequality, education and health outcomes do not show significant effect on poverty. Although, the estimates of inequality, health and education outcomes are insignifi- cant, poverty reduces with inequality but increases with education and health out- comes. The study submits that ECOWAS member countries have not benefited from social inclusive growth strategy in terms of eradicating poverty. Consequently, there is need for urgent and serious effort to promote social inclusion via improved health and education outcomes in addition to reduction in inequality. This will require an overhaul reform in the health and education sectors through improved funding, in- troduction of curriculum tailored at meeting the changing labour market needs and a wage policy that reflects the minimum international standard to improve the overall contribution of health and education to poverty reduction.
Keywords: I15; I25; I32; 330; Education; health; inclusive growth; poverty